Analysis of Technological Innovation and Competitive Advantage in New Energy Vehicle Industry: BYD as an Example - Zhu Lingjie (SHS Web of Conferences)
In the context of global energy transition and carbon neutrality goals, the new energy vehicle (NEV) industry is experiencing rapid growth, with China emerging as the world’s leading market. At the forefront of this transformation, BYD has established itself as an industry benchmark through its vertically integrated supply chain and continuous technological innovation. This paper examines how BYD can enhance its core competitiveness through technological advancements and optimize its capital structure for long-term development, using a mixed-methods approach that integrates financial analysis, competitive landscape evaluation, and technological innovation pathways. The study highlights BYD’s strategic advantages derived from vertical integration in cost control and its comprehensive product portfolio spanning multiple market segments. By combining proprietary technologies such as hybrid systems and electric platforms with capital optimization strategies, BYD demonstrates a sustainable model for market leadership. This research contributes to refining the competitiveness analysis framework for NEV enterprises and provides valuable insights for industry stakeholders and investors navigating the evolving landscape of clean mobility.